EFFECTIVENESS OF MASSAGE WITH VIRGIN COCONUT OIL IN THE PREVENTION OF DECUBITUS ULCERS IN HIGH-CARE UNITS - Wahyudi, Wahid Tri; Savage, Eileen (SYNTIFIC, 2023)
Background. Decubitus ulcers or pressure ulcers are wounds caused by prolonged pressure on the skin due to continuous lying down, which is one of the main causes of mortality and morbidity in patients in health services. Virgin Coconut Oil (VCO) is a method of preventing decubitus ulcers by means of massage which contains natural moisturizers, is easily absorbed by the skin, contains vitamin E and helps maintain skin moisture. This study aims to determine the effectiveness of massage with virgin coconut oil in preventing decubitus ulcers in high-care units. Research Method. Pre-test and Posttest-only with control group design was used as the design in this research. The population in this study was 30 respondents who were divided into two control and treatment groups using an incidental sampling technique. Data collection was carried out by observation during 7 days of treatment of treatment and control respondents in observation sheets according to the EPUAP Pressure Ulcer Classification. Test the hypothesis using the Independent t-test. Findings. The analysis results showed that the P value was 0.005 < 0.05, and there was an influence of virgin coconut oil on the level of pressure ulcers. Conclusion. Early monitoring of symptoms and risks of pressure ulcers so that patients avoid symptoms of pressure ulcers and optimize the patient health status, especially in high-care units.